Persons Responsible For The Supply Of The Army In The Reign Of Amir Temur and Their Duties - Polvanov Azim Kuchkarovich (Pubmedia Social Sciences and Humanities, 2026)
This study examines the military supply system in the state of Amir Temur, focusing on the officials responsible for maintaining logistical support and the specific functions they performed. The success of Amir Temur’s military campaigns depended not only on strategic planning and battlefield tactics but also on a well-organized and efficient supply network that ensured the continuous provision of food, weapons, transportation, clothing, and financial resources to the army. Using historical sources such as Temur’s Regulations, Nizamuddin Shami’s Zafarnama, Sharafiddin Ali Yazdi’s Zafarnama, and other historical accounts, the study analyzes the roles of key officials, including bakovul, muhasib, muhassil, tamgachi, treasurer, yasovul, yurtchi, akhtachi, and ghajirchi. The findings reveal that the Timurid military supply system was highly centralized and operated through a coordinated administrative structure in which each official had clearly defined responsibilities. This organization facilitated effective resource management, secure transportation routes, orderly military encampments, financial control, and disciplined troop movements. The study concludes that the efficiency of this supply system was one of the principal factors behind the success, mobility, and long-term operational stability of Amir Temur’s army during extensive military campaigns.